Thermal Deformation of Granite under Different Temperature and Pressure Pathways - Peng Zhao; Zi-jun Feng (Advances in Materials Science and Engineering)
The thermal cracking of rocks is the phenomenon of expansion and deformation of mineral particles inside the rocks. The thermal deformation of the same granite sample under different heating pathways was meticulously analyzed, and the effect of the variation of external stress on the thermal expansion was carefully studied. The thermal deformation threshold temperature was low under triaxial stress, and a larger expansion was produced under uniaxial stress. The thermal deformation of the rock mass was found to be irreversible. Upon heating to the same temperature, the expansion was found to decrease with the increase in the number of thermal cycles. Besides, for each thermal cycle, the amount of deformation caused by cooling was always greater than the amount of deformation caused by temperature rise; this difference in deformation was especially obvious under a change from triaxial stress to uniaxial stress. In the process of elevated temperature which has the same heating rate, the thermal expansion coefficient was greater under uniaxial stress than it was under triaxial stress; under same external stress, the thermal expansion coefficient with a high heating rate was generally greater than the thermal expansion coefficient with a low heating rate.